2007
DOI: 10.1158/1078-0432.ccr-07-1078
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Is Overexpressed in Advanced Human Prostate Cancer and Necessary for Progressive Growth of Prostate Cancer Cells in Nude Mice

Abstract: Purpose: The purpose of this study was to investigate the potential role of Smad3, a key mediator of transforming growth factor-h signaling, in progression of prostate cancer. Experimental Design: Expression of Smad proteins was determined in human prostate cancer tissue array and cell lines. Growth and metastasis of cells overexpressing dominant-negative Smad3 (Smad3D) were studied to determine its role in tumor progression in mice. Cell growth, apoptosis, and expression of angiogenic molecules in tumor lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 42 publications
(34 reference statements)
1
47
0
Order By: Relevance
“…Recent studies have reported that SMAD3 is overexpressed in PCa tissues and is necessary for progressive growth of PCa cells in nude mice (Lu et al 2007). On the basis of these results and results from other studies showing that MED12 is implicated in TGFb-receptor regulation (Huang et al 2012) and our findings that MED12 has increased expressed in castration-resistant PCa tissues, we aimed to investigate whether MED12 is implicated in TGFb signaling in PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that SMAD3 is overexpressed in PCa tissues and is necessary for progressive growth of PCa cells in nude mice (Lu et al 2007). On the basis of these results and results from other studies showing that MED12 is implicated in TGFb-receptor regulation (Huang et al 2012) and our findings that MED12 has increased expressed in castration-resistant PCa tissues, we aimed to investigate whether MED12 is implicated in TGFb signaling in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of TGFb signaling has been shown to increase the invasive and migratory behavior of PCa cells (Walker et al 2013), and inhibition of TGFb signaling reduced tumor growth and/or invasiveness in vivo (Gaspar et al 2007, Moore et al 2008. Furthermore, a study in 2007 has shown that SMAD-dependent TGFb signaling is critical for PCa growth and progression in nude mice (Lu et al 2007). The response of metastatic PCa cell lines to TGFb depends on the cellular microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b1 functions as a paracrine growth inhibitor in normal cells of the epithelial lineage by inducing cell cycle arrest and apoptosis, and many human cancers escape from TGF-b1-mediated growth suppression by mutational alterations of its receptors or Smads (Markowitz et al, 1995). Unlikely normal epithelial cells, carcinoma cells produce active TGF-b1, which promotes tumor growth, migration and metastasis (Stearns et al, 1999;Zhu and Kyprianou, 2005;Lu et al, 2007;Pu et al, 2009). In prostate tumorigenesis, TGF-b1 has biphasic functions, having a growth inhibitory effect at early stages, but at later stages enhancing the malignant properties of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, both intracellular and serum TGF-b1 levels are elevated in cancer patients and further increased in patients with metastatic carcinoma (Truong et al, 1993). Several studies have shown that prostate cancer cells are resistant to TGF-b1-induced growth inhibition, and TGF-b1 actually promotes tumor growth, migration and metastasis, indicating that TGF-b1 action is oncogenically conversed in the process of tumorigenesis (Stearns et al, 1999;Zhu and Kyprianou, 2005;Lu et al, 2007;Pu et al, 2009). We reported that TGF-b1 promotes cellular proliferation of prostate carcinomas through the activation of Ras/MAPK signaling and induction of tumor-promoting genes, such as interleukin-6, indicating that prostate cancers have a selective growth advantage by autocrine TGF-b1 production (Park et al, 2000(Park et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Many proliferation promoting and protooncogenes are illustrated in these pathways including serine/threonine/ tyrosine kinases, G-protein coupled receptors (GPCs), membrane associated G-proteins, growth factors; DNA-binding protein factors and transcription factors as well. A large number of genes grouped under AbG-0.5 kb gene group such as CDC20 (Cell Division Cycle 20), SMC1A (Structural Maintenance of Chromosomes 1A), BUB1 (budding uninhibited by benzimidazoles 1) and SMAD3 (Mothers against Decapentaplegic Homolog 3) are known to promote cell cycle progression and proliferation in different cancer types [80][81][82][83]. Gene Ontology (GO) classification and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis also reported that AGO1-regulated genes (ArGs), regulate various cancer related pathways and they shared this with AbGs-5 kb genes including cell cycle regulation, MAPK signalling pathway, p53 signaling pathway in various cancers Regulation of pre-mRNAs by MALAT (Metastasis Associated Lung Adenocarcinoma Transcript 1) was the first demonstration of the regulation of alternative splicing by endogenous sRNA pathways [63].…”
Section: Ago1 Machinery Genes and Cancer-related Pathwaysmentioning
confidence: 99%